2019
DOI: 10.22456/1982-8918.85297
|View full text |Cite
|
Sign up to set email alerts
|

Igualdad De Género Y Análisis De La Comunicación Motriz en Las Tareas De La Educación Física

Abstract: Este artigo analisa as tarefas motoras propostas no âmbito da Educação Física, tanto pelo professor quanto no jogo livre, a partir de uma perspectiva de gênero. A partir de uma observação participante, obtêm-se as tarefas propostas nas sessões de Educação Física de uma escola na cidade de Meliana, na província de Valência (Espanha). São analisadas e contextualizadas 134 tarefas motoras na estrutura educacional. Os resultados mostram que há uma tendência a promover um certo modelo de comportamento comum quando … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…Several authors have highlighted this need, including Blández,Fernández,and Sierra [20], García [21], and Alfaro, Bengoechea, and Vázquez [22]. The results showed that by providing tasks and activities that are presented in an attractive way for girls, their confidence, motivation, enjoyment, problem-solving skills, and self-control can be improved [37]. Therefore, it is necessary to provide strategies to bridge the existing gap between male-dominated activities and those that girls may find interesting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors have highlighted this need, including Blández,Fernández,and Sierra [20], García [21], and Alfaro, Bengoechea, and Vázquez [22]. The results showed that by providing tasks and activities that are presented in an attractive way for girls, their confidence, motivation, enjoyment, problem-solving skills, and self-control can be improved [37]. Therefore, it is necessary to provide strategies to bridge the existing gap between male-dominated activities and those that girls may find interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Pelegrin et al [33] researched these factors with the aim of finding a way to promote gender equality. Rodríguez and Miraflores [35] and Granda et al [36] designed instruments and approaches to try to overcome stereotypes and inequalities in student perception, while Gil and Etxebeste [37] analyzed teachers' work with a view towards promoting changes in favour of greater gender equality. The Table 2 summarizes these investigations regarding objectives, methodology, results, and conclusions reached by them:…”
Section: Gender Equality In Physical Education In Schoolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Al analizar el estado de la cuestión, estudios realizados en educación básica, refieren múltiples factores psicosociales vinculados a una menor práctica físico-deportiva por parte de las estudiantes de género femenino (Bravo et al 2016;Vicente-Pedraz y Paz Brozas-Polo, 2017). Investigaciones han identificado de manera comparativa durante la clase de educación física, que las niñas presentan un negativo autoconcepto, menor autonomía y competencia que los niños (Gómez Rijo et al, 2014), también, menor intención de participar activamente en tareas motrices (Gil Quintana y Etxebeste Otegi, 2019, Zueck Enríquez et al 2019; Barajas Pineda et al 2021).…”
Section: Introductionunclassified